Atypical Femur Fracture: Correlation between Bisphosphonates Users and Nonusers - Kamal, Dr. Salim (International Journal of Innovative Research in Medical Science, 2017)
Medications to treat and prevent osteoporosis, such as bisphosphonates, are now being increasingly used. This drug can prevent common osteoporotic fractures in patients with osteoporosis, particularly in the hip and vertebrae. But recently it has been found that bisphosphonate-related suppression of bone remodeling may adversely influence bone strength. The pathogenicity of atypical femoral fractures is due to the accumulation of microdamage which leads to homogeneity in bone tissue and there is low homogenecity due to use of bisphosphonates and subsequently leads to lower bone quality. However, the association between long-term use of bisphosphonates and atypical femoral fractures is still doughtful and lots of studies have showed variability in relative risk factors. Stress fractures which have been well recognized to be caused by bowing deformity may also be classified as atypical femoral fractures. Therefore this study was done to investigate and to compare clinical characteristics and surgical outcome of atypical femoral fractures associated with patients on bisphosphonates and those of fractures not associated with bisphosphonates use. Material and Methods: A total of 46 patients who had been operatively treated for a complete atypical femoral fracture were identified. Patient information, including clinical manifestations, medication history, radiographic characteristics, operative methods, treatment outcome and follow-up results were recorded. Bisphosphonates use was stopped after atypical fracture was diagnosed, but calcium supply was continued. Perioperative clinical assessment was performed. Radiological assessment was done by taking radiographs postoperatively at 1, 2, 3, 6, 9 month and 1 year post operation. Results: A total of 46 patients with atypical femoral fracture were enrolled in the study. of which 41 patients were having history of bisphosphonate use while 5 were not using the drug. Average Duration of Bisphosphonate use (in years) was 3.85.Time to union in patients on bisphosphonates was 5.23 months while 24(52.17%) achieved union at six months. In one patient implant failure was found. Neither in patients who were nor taking bihosphonate drugs. Out of 41 biphosphonate group patients 24(52.1%) achieved complete bony union within 6 months, while in non bisphosphonate user complete union in six months was 4 (80%). Conclusion: In conclusion of 46 patients 24(52.17%) patients on biphosphonats showed bony union and 4 (80%) showed bony union within 6 months after the index surgery. There was no difference in bony union rate between the biphosphonate group and the non-biphosphonate group.